Do financing constraints hinder corporate fixed investment? Evidence from the Amman stock exchange - Mohammad A. Khataybeh (Cogent Business & Management, 2021)
This research provides new evidence on financing constraints on corporate fixed investment by emphasizing the role of cash holdings as a precautionary source of funds. Applying GMM estimates to a sample of 106 Jordanian firms, the results suggest that firms follow trade-off theory in financing their investments but are financially constrained. The coefficient of the cash holdings variable appears to be negative in the fixed-investment regression, suggesting that when firms face financing shocks, they draw upon their precautionary cash reserves to smooth the path of their expenditure on fixed assets.
Keywords: G11; G30; G32; 650; cash holdings; financing constraints; fixed investment; cash holdings; financing constraints; fixed investment